The Relationship Between Students’ Perception of a School as a Caring Community and Academic Motivation - Buterin Mičić, Marija (Pedagogika, 2023)
This paper examines the relationship between students’ perception of school as a caring community and their motivation in the academic domain. Data were collected using a questionnaire among 434 students of upper primary school grades from Croatia. The results of the research indicate that students who perceive school as a caring community more positively are more autonomously motivated to perform school obligations.